(untitled) (JBIOEDRA: Jurnal Pendidikan Biologi, 2025)
This review article aims to examine research findings on the macronutrient content (carbohydrates, proteins, and fats) and vitamins of various Indonesian local food products, including analog rice flour biscuits, red dragon fruit crackers, potato balls, instant rice bran porridge, Chaguro seasoning powder, and processed pedada fruit. The review methodology involved the selection of eight national journal articles obtained from academic databases and university lecturer publications. Article retrieval was conducted using the keywords “macronutrients,” “proximate analysis,” and “local food,” covering publications from 2011 to 2025. Inclusion criteria comprised experimental or laboratory-based analytical studies focusing on local food products with reported macronutrient data, while conceptual articles without laboratory analysis were excluded. The review results indicate considerable variation in nutritional composition among local food products. Carbohydrate content was highest in analog rice biscuits (67.19%), protein content was relatively high in potato balls (27% of the recommended daily intake), and fat content was notably high in analog biscuits (18.42%). Fresh pedada fruit showed high carbohydrate content (77.6%) and was rich in vitamin C (56.74 mg/100 g). Overall, the reviewed studies demonstrate a trend toward substituting local ingredients such as cassava, maize, seaweed, pedada, chayote, tuna, and rice bran to enhanceand protein content. However, differences in formulation and analytical methods contributed to variability in nutritional values across studies.